Collective-Consumption Services of Individual-Consumption Goods: Comment - Long, Millard F. (Quarterly Journal of Economics, 1967)
Journal Article Collective-Consumption Services of Individual-Consumption Goods: Comment Get access Millard F. Long Millard F. Long University of Chicago Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 81, Issue 2, May 1967, Pages 351–352, https://doi.org/10.2307/1879595 Published: 01 May 1967